Interspecies Reconstructed Embryonic Cell Interaction between Campbell Hamster (Phodopus campbelli) and Mice (Mus musculus) - Noer Muhammad Dliyaul Haq; Diah Pristihadi; Vista Budiariati; Dwi Budiono; Al Mukhlas Fikri; Mokhamad Fahrudin; Cece Sumantri; Arief Boediono (Bogor Agricultural University, Indonesia, 2021)
Interspecies embryo transfer is a seldom-used method to increase the successful conservation of endangered species. The study aimed to determine the potential development of interspecies reconstructed embryos. The present study used two animal models, Campbell hamsters (Phodopus campbelli) and mice (Mus musculus). The isolated inner cell mass (ICM) of hamster embryos were injected into the mice embryos. The embryos were transferred to the pseudopregnant mice using non-surgery embryos transfer methods. The fetuses were collected at day 13.5 of gestation for morphometric measurement and cytochrome b (Cyt b) analysis which used to determine the species of obtained fetuses. The results showed that the viability, pregnancy rate, and embryonic implantation ability of the interpecies reconstructed embryos did not differ significantly (p>0.05) compared to non-reconstructed embryos. Morphometric measurement showed that the crown-rump (CR) and the weight of fetuses in the reconstructed group were significantly higher than non-reconstructed group (p<0.05). According to Cytb analysis, the species of obtained fetuses were mice, while the population of hamster cells were found only in the blighted ovum (resorption). Therefore, it can be concluded that interspecies reconstructed embryos are able to implant. However, the population of mice cells are only found to develop.